(untitled) (Scientific journal of the Fergana State University, 2026)
The Jadid movement is a social, political and cultural movement that promoted new ideas of enlightenment and development in Uzbek society in the late 19th and early 20th centuries. This article analyzes the activities of the movement in the education system, press and upbringing. The Jadids made a great contribution to the upbringing of a new generation by developing national, modern education, updating the Arabic script and opening many schools. Through the press, they popularized their modern and progressive ideas and promoted national revival and cultural reforms. Through reforms in education and upbringing, the Jadid movement allowed the Uzbek people to understand their identity, integrate with the modern world, and step into science and culture. The article also examines the philosophical aspects of this movement and its connection to the present day.